The road to Gandolfo - Ludlum, Robert (London : Orion fiction, 2010)
The Road to Gandolfo by Robert Ludlum is a humorous and satirical novel that follows General MacKenzie Hawkins, a mischievous and cunning retired army general, as he concocts an elaborate scheme to kidnap the Pope. Filled with witty dialogue, clever plans, and unexpected twists, the story combines adventure, comedy, and satire, showcasing Ludlum$1 (Bs lighter side compared to his usual thriller novels. The book entertains readers with clever antics, absurd situations, and larger-than-life characters, making it a fun, fast-paced read for teens and adults alike.s